Incidental traumatic right diaphragmatic rupture: a missed case after trauma - Fatima Alharmoodi; Shadin Ghabra; Salem Alharthi (Journal of Trauma and Injury)
Traumatic diaphragmatic hernia is among the most uncommon conditions after severe trauma, and it is associated with high morbidity and mortality. The diagnosis is difficult and might be missed, but a multimodal investigation might help in terms of diagnostic yield. In this case report, we present a missed right diaphragmatic rupture 14 years after the trauma.